Environmental Security in Harbors and Coastal Areas Management Using Comparative Risk Assessment and Multi-Criteria Decision Analysis - Linkov, Igor.; Linkov, Igor.; Kiker, Gregory A.; Kiker, Gregory A.; Wenning, Richard J.; Wenning, Richard J. (Nato Security through Science Series C, Environmental Security, 2007)
Human experience has shown how great cities, nations, and empires have either collapsed or retired from their predominant stature when natural resources are depleted to an extent that exceeds the ability of the environment to restore or replenish their supply. This book explores the challenges facing coastal areas during the next few decades and the difficult decisions needed to prevent a repeat of the past. Establishing, maintaining or enhancing a sense of environmental security in different coastal regions and improving the management of critical infrastructure will require (i) matching human demands with available environmental resources; (ii) recognition of environmental security threats and infrastructure vulnerabilities; and, (iii) identification of the range of available options for preventing and/or minimizing natural disasters, technological failures, and/or terror actions. This book emphasizes beliefs that the convergence of seemingly disparate viewpoints and often uncertain and limited information is possible only by using one or more available risk assessment methodologies and decision-making tools such as multi-criteria decision analysis (MCDA).